Comparative ecology and behaviour of Chamaeleo pumilus pumilus (Gmelin) and C. namaquensis A. Smith (Sauria: Chamaeleonidae) - Burrage, Bryan Ronald (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 1972.